Clinical Outcomes of Revision Posterior Lumbar Interbody Fusion for Late Deterioration after Laminotomy Assessed with the Zurich Claudication Questionnaire - Sakaura, Hironobu; Fujimori, Takahito; Sugiura, Tsuyoshi; Yamada, Shutaro; Kanayama, Sadaaki; Ikegami, Daisuke (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2025)
A retrospective analysis of prospectively collected data.There have been a few studies comparing surgical outcomes between revision lumbar fusion surgery and the same primary surgery.Using the Zurich Claudication Questionnaire (ZCQ), we compared clinical outcomes of revision posterior lumbar interbody fusion (PLIF) for late deterioration after laminotomy with those of primary PLIF to examine whether surgical outcomes of revision PLIF for late deterioration after laminotomy are inferior to those of primary PLIF.Sixteen consecutive patients undergoing revision single-level PLIF for late deterioration after single-level laminotomy (R group) and 61 consecutive patients undergoing primary single-level PLIF during the same period (P group) were enrolled. Before PLIF surgery and at 2 years postoperatively, clinical outcomes were assessed using the ZCQ. Achievement rates of the minimum clinically important difference (MCID) of each domain (Symptom severity [SS] and Physical function [PF]) on the ZCQ were calculated in each group.In the R group, mean SS and PF before revision PLIF and at 2 years after surgery were 3.429 and 2.8, and 1.946 and 1.6, respectively. In the P group, mean SS and PF before primary PLIF and at postoperative 2 years were 3.438 and 2.5, and 2.194 and 1.6, respectively. Both SS and PF significantly improved at postoperative 2 years in both groups, and SS both before and after PLIF and PF at 2 years postoperatively showed no significant differences between the two groups. Achievement rates of the MCID of SS and PF were 81.3 and 68.8% in the R group, and 59.0 and 59.0% in the P group, respectively. None of the MCID achievement rates of SS and PF showed significant differences between the two groups.Clinical outcomes of revision PLIF for late deterioration after laminotomy were equivalent to those of primary PLIF assessed with the ZCQ at 2 years after PLIF surgery.
Keywords: clinical outcomes; Zurich Claudication Questionnaire; posterior lumbar; interbody fusion; revision surgery; primary surgery